2008
DOI: 10.1111/j.1439-0531.2007.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Selenium Supplementation on the Reproductive Performance in Synchronized Merino Sheep at Range Conditions in a Selenium‐deficient Area

Abstract: The effect of selenium (Se) supplementation on the reproductive performance of Merino ewes mated out of the normal breeding season was studied in a 2 (no Se supplementation vs Se supplementation) x 2 (ewes mated at natural oestrus vs synchronized oestrus) factorial design with 50 ewes per treatment combination. Synchronization of oestrus was achieved by intravaginal insertion of 40 mg cronolone sponges for 14 days and administration of 440 IU PMSG at sponge withdrawal. Se supplementation was by the addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The previously reported negative effects of Se supplementation on ewe reproduction may be because van Niekerk et al (1996) used a very high dosage of Ba-selenite (one time injection of 50 mg Se as Ba-selenite; no signifi cant effect of injecting 1 mg Se as Na-selenite) administered 18 to 35 d after mating to achieve the decrease in conception rates. Sánchez et al (2008) observed that estrus synchronized ewes receiving 0.125 mg Se/d as SeMet in the diet had lower conception and lambing rates than estrus synchronized ewes receiving no Se supplement, although naturally mated and Se-supplemented ewes had similar conception and lambing rates, compared with non-Sesupplemented ewes. Therefore, we conclude that there is little evidence to suggest a detrimental effect of supranutritional Se supplementation at dosages up to 24.5 mg Se/wk.…”
Section: Effect Of Selenium On Ewe Reproductive Performance and Healthmentioning
confidence: 91%
See 2 more Smart Citations
“…The previously reported negative effects of Se supplementation on ewe reproduction may be because van Niekerk et al (1996) used a very high dosage of Ba-selenite (one time injection of 50 mg Se as Ba-selenite; no signifi cant effect of injecting 1 mg Se as Na-selenite) administered 18 to 35 d after mating to achieve the decrease in conception rates. Sánchez et al (2008) observed that estrus synchronized ewes receiving 0.125 mg Se/d as SeMet in the diet had lower conception and lambing rates than estrus synchronized ewes receiving no Se supplement, although naturally mated and Se-supplemented ewes had similar conception and lambing rates, compared with non-Sesupplemented ewes. Therefore, we conclude that there is little evidence to suggest a detrimental effect of supranutritional Se supplementation at dosages up to 24.5 mg Se/wk.…”
Section: Effect Of Selenium On Ewe Reproductive Performance and Healthmentioning
confidence: 91%
“…There are some concerns that additional Se supplementation in ewes with adequate Se status may negatively affect embryonic survival shortly after conception through an unknown mechanism (van Niekerk et al, 1996;Sánchez et al, 2008;Palmieri and Szarek, 2011). Davis et al (2006a,b) addressed these concerns by feeding ewes throughout 2 lambing seasons with up to 20 mg Se/kg of diet as fed of Na-selenite, dietary Se concentrations much greater than in our study, and did not detect detrimental effects on ewe conception rates.…”
Section: Effect Of Selenium On Ewe Reproductive Performance and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be explained by maintaining the antioxidant status of the EMMH supplemented animals from loss during heat stress conditions. Antioxidants supplementation are free radical scavengers, which protect the body defense system against excessively produced free radicals during heat stress and stabilize health status of the animal (Sánchez et al, 2008). Furthermore, it was reported that probiotics stabilize healthy microbial balance in the intestine which leads to improve animal efficiencies especially in stressed animal which face heat stress or feed on toxic or improper diets (Zinedine et al, 2005).…”
Section: Thermal Responses Respiratory Activities and Heat Productiomentioning
confidence: 99%
“…Maternal nutrient restriction caused by heat stress during certain periods of gestation can have significant bad impact on placental and fetal growth and development (Reynolds et al, 2010). Also, free radicals and reactive oxygen species play a number of significant and diverse roles in reproductive biology (Sánchez et al, 2008). Moreover, lower levels of the antioxidant is associated with poor fertility in ruminants (Nayyar and Jindal, 2010).…”
Section: Reproductive Traitsmentioning
confidence: 99%